Genetic Parameter Estimation and Whole Sequencing Analysis of the Genetic Architecture of Chicken Keel Bending - Zhang, Zhihao; Yang, Weifang; Zhu, Tao; Wang, Liang; Zhao, Xiaoyu; Zhao, Guoqiang; Qu, Lujiang; Jia, Yaxiong (Frontiers in Genetics, 2022)
Bone health is particularly important for high-yielding commercial layer chickens. The keel of poultry is an extension of the abdomen side of the sternum along the sagittal plane and is one of the most important bones. In this study, the keel phenotype of White Leghorns laying hen flocks showed significant individual differences. To clarify its genetic mechanism, we first estimated the heritability of keel bend (KB) in White Leghorn and examined the blood biochemical indexes and bone quality, and then performed whole-genome pooled sequencing (Pool-Seq) on two groups of chickens with different keel phenotypes. We then performed selection elimination analysis to determine the genomic regions that may affect the keel phenotypes. The results showed that KB was a medium heritability trait. The content of parathyroid hormone was lower (P < 0.01) and that of calcitonin was higher (P < 0.01) in KB chickens than that in keel normal (KN) chickens. The differences in bone mineral density, bone strength, and bone cortical thickness of the humerus and femur were extremely significant (P < 0.01), with all being lower in KB chickens than those in KN chickens, and the bones contained more fat organization in KB chickens. A total of 128 genes were identified in selective sweep regions. We identified 10 important candidate genes: ACP5, WNT1, NFIX, CNN1, CALR, FKBP11, TRAPPC5, MAP2K7, RELA, and ENSGALG00000047166. These results may help us to better understand the molecular mechanism of bone traits in chickens and other birds and provide a new idea for the genetic breeding of chickens.